Το οπτικοακουστικό έργο “Το Αιγαίο στις φλόγες”, ως μέσο για την ευαισθητοποίηση των μαθητών για την ιστορία του Αιγαίου. - Κεραμιδάς Παναγιώτης; Κουτσοτόλη Ιωάννα; Κουρκουλιώτη Παναγιώτα; Κυριάκος Παναγιώτης; Πανουσέρης Θωμάς; Κανύχης Παναγιώτης (Open Journal of Animation, Film and Interactive Media in Education and Culture [AFIMinEC], 2022)
The general purpose of this article is to provide a sufficient analysis regarding to the educational film “ΤοΑιγαίοστιςφλόγες” (Aegean on fire). Through the observation of the fundamental elements of the film and the methods applied for its creation, the overall value of this film for the interdisciplinary teaching of history is evaluated.In this particular film there will be a historic retrospection regarding the most famous and important naval battles that happened in the Aegean sea. Starting from the ancient times we have a reference for the battles of Artemisio and Salamina at 480 B.C. Additionally there is a description for the naval conflicts of Mykali at 479 B.C. and Arginousses as well as the Aigos Rivers. Going through the period of the Byzantine empire, there is a reference of the battles of the Corinthian Bay and of the Handakas of Crete. During the age of the Ottoman Rule, the battle for Andros was worth mentioning while the battle of Gerondas and many others from the Greek revolution have also been showcased.Lastly, in the Balkan Wars era, three are the most significant events of naval combat. The first one was the submersion of the warship Fetich Boulen on 18 October 1912, then we have the story of the Averofwarship and the third milestone is the naval battle for Limnos. Moreover there is a reference for the significant achievements of the Katsonis and Papanikolis submarines as well as the torpedo-destroyers Andrias and Queen Olga during the second World War.